Comparison of dimethyl fumarate and interferon outcomes in an MS cohort - Sattarnezhad, Neda; Healy, Brian C.; Baharnoori, Moogeh; Diaz-Cruz, Camilo; Stankiewicz, James; Weiner, Howard L.; Chitnis, Tanuja (BMC neurology, 2022)
Background To compare the effectiveness of dimethyl fumarate (DMF) with subcutaneous interferon beta-1a (IFNβ-1a) in controlling disease activity in patients with relapsing–remitting Multiple Sclerosis (MS). Methods Clinical and imaging data from patients treated with either IFNβ-1a or DMF for at least one year were reviewed. The proportion of patients with at least one clinical relapse within 3–15 months after treatment onset, the proportion of patients with new T2 or gadolinium-enhancing lesions, and the proportion of subjects who achieved no evidence of disease activity (NEDA) status were assessed. Results Three hundred sixteen (98 on IFNβ-1a, 218 on DMF) subjects were included. Baseline demographics were comparable between groups except for age, disease duration, and the number of previous treatments being higher and relapse rate in the prior year being lower in the DMF-treated group. The proportion of patients having a clinical relapse (24.5% vs. 9.6%; OR = 3.04; P < 0.001) or a new MRI lesion (28.6% vs. 8.7%; OR = 4.19, P < 0.001) at 15 months were higher on IFNβ-1a. 79.9% of the patients achieved NEDA status at 15 months on DMF (vs. 51.1% for IFNβ-1a; OR = 0.26, P < 0.001). Further adjustment for demographics, disease characteristics, treatment and relapse history, and subgroup analyses confirmed these findings. Conclusion DMF was associated with less clinical and radiological disease activity compared to IFNβ-1a.